CIGB-552: Anticancer peptide with multimodal mechanisms and clinical promise for colorectal cancer - J. R. Fernandez Masso; B. Oliva Arguelles; M. Carpio Alvarez; F. Hernandez Bernal; M. Limonta Fernández; H. Yueming; M. Chen; D. I. Chelovsky (Исследования и практика в медицине)
Despite advances in chemotherapy and targeted therapy, resistance and systemic toxicity limit the clinical efficacy of current treatments of colorectal cancer (CRC).Purpose of the study. To analyze published experimental studies on the peptide drug CIGB‑552, which targets COMMD1, and its potential use in the treatment of CRC.Materials and methods. We conducted a literature search in NCBI MedLine (PubMed), Google Scholar, and Web of Science databases using a list of keywords that included: «CIGB‑552», «COMMD1», «NF-κB», «inflammation», «HIF1A», «hypoxia», «SOD1», «oxidative stress» and “colorectal cancer”. Original studies and reviews published in the last five were used, except for publications related to CIGB‑552, for which all studies published since 2013 were reviewed.Results. Analysis of literature shows that the peptide CIGB‑552 inhibits NF-κB via COMMD1‑mediated ubiquitination of RELA and stabilization of NFKBIA, suppresses HIF1A-driven angiogenesis, and disrupts SOD1 activity to induce oxidative stress. Preclinical studies demonstrated tumor regression in xenograft models and disease stabilization in pet dogs with spontaneous tumors. Synergistic effects with chemotherapy were observed in vitro and in vivo, enhancing apoptosis and chemosensitivity. In the Phase I clinical trial, the main adverse event was a transient, mild pruritic rash, without hematological or organ toxicity. Pharmacokinetic data showed rapid clearance of the peptide from the circulation, suggesting long-term effective use. Mechanistic studies suggest preferential activity of the peptide in aggressive CRC subtypes: CMS4 and CMS1.Conclusion. CIGB‑552's multimodal targeting of NF-κB, HIF1A, and oxidative stress impacts key resistance mechanisms in CRC, particularly in KRAS- or BRAF-mutated tumors (30–50 % of cases). The favorable safety profile, synergistic potential with chemotherapy, and predicted efficacy in high-risk subtypes warrant expanded clinical evaluation to optimize dosing and confirm therapeutic benefit.